# (a+b+c)2=a2+b2+c2+2ab+2b+2ca---verify

2
by Deleted account
with all the steps plz

2014-10-01T21:54:59+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(a+b+c)²
=(a+b+c) × (a+b+c)
=[a×(a+b+c)] + [b×(a+b+c)] +[c×(a+b+c)] (by distributive law)
= [a² + ab + ac] + [ ba +b² + bc] + [ ca + cb + c²]
= a² + ab + ac + ba +b² + bc + ca + cb + c²
= a² + ab + ac + ab +b² + bc + ac + bc + c²   (ab=ba)
= a² + b² + c² + ab + ab + bc + bc + ac + ac
= a² + b² + c² + 2ab + 2bc + 2ca
ok now?
its enough if u can add more its better
thank u i will surely mark as best
:P
thank alot thank u
2014-10-02T07:45:54+05:30
(a+b+c)²

let a+b=x  ,c=y

substitute the values in the equation

(x+y)²=x²+y²+2xy

(a+b)²+c²+2c(a+b)

a²+b²+2ab+c²+2ac+2bc

a²+b²+c²+2ab+2bc+2ca